2017
DOI: 10.1071/rd15270
|View full text |Cite
|
Sign up to set email alerts
|

Inducing ovulation with oestradiol cypionate allows flexibility in the timing of insemination and removes the need for gonadotrophin-releasing hormone in timed AI protocols for dairy cows

Abstract: The effects of addition of gonadotrophin-releasing hormone (GnRH) to a progesterone plus oestradiol-based protocol and timing of insemination in Holstein cows treated for timed AI (TAI) were evaluated. Cows (n=481) received a progesterone device and 2mg oestradiol benzoate. After 8 days, the device was removed and 25mg dinoprost was administered. Cows were allocated to one of three (Study 1; n=57) or four (Study 2; n=424) groups, accordingly to ovulation inducer alone (Study 1; oestradiol cypionate (EC), GnRH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
(70 reference statements)
0
4
0
1
Order By: Relevance
“…Other studies have shown that, despite these differences in circulating E2 profiles, ovulation rate did not differ between E2 esters and the expected time of the ovulation was also similar (~72 h after intravaginal P4 implant removal; Baruselli et al, 2012). When EC was compared with GnRH at the end of the E2/P4 FTAI protocol, ovulation rate also did not differ between treatments (Ferreira et al, 2017). Furthermore, P/AI did not differ when EB and EC were compared at the end of the protocol .…”
Section: Resultsmentioning
confidence: 85%
“…Other studies have shown that, despite these differences in circulating E2 profiles, ovulation rate did not differ between E2 esters and the expected time of the ovulation was also similar (~72 h after intravaginal P4 implant removal; Baruselli et al, 2012). When EC was compared with GnRH at the end of the E2/P4 FTAI protocol, ovulation rate also did not differ between treatments (Ferreira et al, 2017). Furthermore, P/AI did not differ when EB and EC were compared at the end of the protocol .…”
Section: Resultsmentioning
confidence: 85%
“…GnRH at the end of the E2/P4 FTAI protocol, ovulation rate did not differ between treatments, as well (FERREIRA et al, 2015). Furthermore, P/AI did not differ when EB and ECP were compared at the end of the protocol (MELO et al, 2016).…”
Section: Resultsmentioning
confidence: 79%
“…Ainda, foi verificado por Gimenes et al (2008) (SOUZA et al, 2009). Da mesma forma, outros estudos não encontraram diferenças na taxa de ovulação após o tratamento com GnRH ou CE em vacas Nelore (MENEGHETTI et al, 2009) e Holandesa (SOUZA et al, 2009FERREIRA et al, 2015).…”
Section: Discussionunclassified